Geometrical Confinement Effects in Layered Mesoscopic Vortex Matter - Cejas Bolecek, N.R.; Dolz, M.I.; Kolton, A.; Pastoriza, H.; Beek, C.Jvander; Konczykowski, M.; Menghini, M.; Nieva, G.; Fasano, Y.; Fasano, Yanina; Nieva, Gladys (Springer Nature, 2015)
Fil: Cejas Bolecek, N.R. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina